2020
DOI: 10.29252/jafm.13.03.30551
|View full text |Cite
|
Sign up to set email alerts
|

Design for a Squirrel Cage Fan with Double Arc Blade

Abstract: Squirrel cage fans are commonly used in HVAC (heating, ventilation, and air conditioning) systems. The single arc blade model is commonly used in this type of fans since it can be shaped simply only by two parameters of inlet and outlet angle of blade. However, the efficiency of the fans is much lower than that we expected. In this paper, the single arc blade is replaced by double-arc blade in order to optimize the blade model and to improve the static pressure efficiency and total pressure efficiency of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The photograph of the testing site and a schematic diagram are presented in Figur 2. The static pressure of the fan is determined by measuring the pressure differential be tween the positive and negative pressure chambers using a pressure sensor, while the flow rate is calculated based on nozzle parameters [18,19]. The muffler section of each air cham ber is equipped with four pressure measurement points.…”
Section: Fan Test Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The photograph of the testing site and a schematic diagram are presented in Figur 2. The static pressure of the fan is determined by measuring the pressure differential be tween the positive and negative pressure chambers using a pressure sensor, while the flow rate is calculated based on nozzle parameters [18,19]. The muffler section of each air cham ber is equipped with four pressure measurement points.…”
Section: Fan Test Methodsmentioning
confidence: 99%
“…The pressure is determined as the average of four monitoring holes strategically positioned on the circumferential section of the chamber at a specific distance ahead and behind the nozzles. The flow rate Q m is calculated by the ∆P st in front of and behind the nozzles [18,20].…”
Section: Fan Test Methodsmentioning
confidence: 99%
“…χ 1 and χ 2 in Table 5 are used as a set of variables, and stress is used as a variable y, which is substituted into formula (7), it can be obtained that the multiple correlation coefficient between the stress of weld 1 and the position of side column 1 and side column 2 is 0.89. Similarly, according to the data of Table 6, the multiple correlation coefficient of the stress of weld 2 and the position of side column 1 and side column 2 is 0.66.…”
Section: Correlation Analysis Based On Multiple Correlation Coefficientmentioning
confidence: 99%
“…(a) The crack on cross bearer weld of 70t gondola car body, (b) The crack on cross bearer weld of 80t gondola car body At present, scholars have mainly studied the structural asymmetry in the fields of towers, bridges, composite materials, etc. [2][3][4][5], and there are only a few scholars who have researched on the structural asymmetry of ships, buses, and other mechanical structures [6][7][8]. The methods used in these studies can be mainly summarized as follows: finite element simulation is used to analyze and evaluate the influence of asymmetric structure on the stress, stiffness, frequency, etc.…”
Section: Introductionmentioning
confidence: 99%
“…An interesting finding revealed that the dominant patterns of jet-wake flow were caused by vortex and blade channel blockage, resulting in high velocities on the pressure side of the blade [13]. The orthogonal method has also been employed to improve the number of blades, manufacturing parameters of fan blades, and aerodynamic performance of fans [14,15]. Xu et al [16] investigated the impact of different blade tilt angles on the performance of centrifugal compressors.…”
Section: Introductionmentioning
confidence: 99%